Histological Effects of SD Rats Liver Tissue Upon Exposure to Xylene - Yasrul Izad, Abu Bakar; Mohd Harissal, Ismail; Nurul Aiman, Mohd Yusof; Hasmah, Abdullah (2016)
lntroduction; Xylene is an aromatic hydrocarbon known for its wide usage in tissue processing, staining and cover slipping in the histology laboratory. Xylene is also considered as environmental contaminants, as it can be identified in the atmosphere and in surface and treated waters. At very high levels of exposure, xylene can injure the liver. Methods: Twelve 28 days old female Sprague-Dawley rats were divided into control and xylene group. The xylene group was given 8.47 mmol/kg/day of xylene in olive oil vehicle via oral gavage for 2 weeks. Then, the rats were sacrificed and the sections of liver were stained. Results: The study found that there was a significant difference (P<0.05) in the distance between portal triad and central vein. Conclusion: In conclusion, the present study has confirmed that xylene exposure can cause significant hepatotoxic effect on liver as evidence by the cellular reduction of hepatocyte in order to congestion and reduce length of hepatocytes.